Comparing the influence of early and late time-restricted eating with energy restriction and energy restriction alone on cardiometabolic markers, metabolic hormones and appetite in adults with overweight/obesity: per-protocol analysis of a 3-month randomized clinical trial - Bernarda Habe; Tanja Črešnovar; Ana Petelin; Saša Kenig; Nina Mohorko; Zala Jenko Pražnikar (Nutrition & Metabolism)
Abstract Background It remains unclear whether adding time-restricted eating (TRE) to energy restriction (ER) offers additional cardiometabolic benefits, particularly in metabolic hormone regulation, and insulin sensitivity. This per-protocol analysis assessed whether early TRE (eTRE) or late TRE (lTRE), when combined with ER, additionally improves insulin resistance indexes, and cardiovascular and liver biomarkers compared to ER alone. Methods We analysed per-protocol data of 90 participants, 31 from the eTRE with ER (eTRE + ER) group, 28 from the lTRE with ER (lTRE + ER) group and 31 from the ER group. As chronotype-adapted diets have already been shown to produce better outcomes than non-adapted ones and in line with real-life behaviour, randomisation was performed on the basis of the individuals’ chronotype. Anthropometric and biochemical measurements for analysis were taken at baseline, and after first and third month of intervention. The primary outcome was mean change in body mass, while the secondary outcomes were mean changes in glycaemic markers (fasting glucose, fasting insulin), indexes of insulin resistance, cardiovascular and liver markers and metabolic hormones (adiponectin, ghrelin, leptin, leptin/ghrelin ratio). Additionally, participant’s subjective appetite was also assessed at baseline and in third month of the intervention. Results We confirmed that participants who adhered to eTRE + ER for 3 months showed greater improvements in % of fat mass, BMI, and fasting glucose compared to those in the lTRE + ER and/or ER group. These greater reductions in % of the fat mass and BMI were accompanied by more pronounced decreases in leptin levels, with eTRE + ER showing larger leptin reductions than lTRE + ER or ER. Additionally, the eTRE group showed a significantly greater decrease in desire for food and greater reduction in capacity to eat than ER. However, insulin levels, insulin resistance indexes, lipid profiles, adiponectin, ghrelin, visceral fat indexes, and liver enzymes showed similar changes across all groups. Conclusions This analysis showed that eTRE + ER is more effective weight management strategy, while eTRE + ER, lTRE + ER and ER are comparable effective on cardiovascular, liver and insulin resistance markers. Trial registration https://clinicaltrials.gov/study/NCT05730231 (NCT05730231, registered on February 6, 2023).